Pola Penerimaan Ujian Nasional Berbasis Komputer (UNBK) Terhadap Siswa SMK Prapanca Dengan Menggunakan Metode Unified Theory Of Acceptance And Use Of Technology (UTAUT) - Sandria, Islamu Fahmi; Slamet, Slamet; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Ujian Nasional Berbasis Komputer (UNBK) requires participants to use computer media in the implementation with the aim of facilitating students to do exam questions and save time of workmanship, one of which users are participants from students of SMK Prapanca Surabaya. Many problems still make the students can not accept the performance of UNBK, that is students less understand the problems by using CBT (Computer Based Test), lack of understanding of the features that exist in the application, and less know the information technology system. In order to know the level of acceptance of students in receiving the performance of UNBK system, it is necessary to census 65 students of SMK Prapanca Surabaya by spreading questionnaires that apply the method of UTAUT (Unified Teory of Acceptance and Use of Technology), which is based on Performance Expectation, Effort Expectation, Social Influence , Facilitating Conditions, Behavioral Intention and Use behavior. The result of the questionnaire is processed by statistical test that is descriptive analysis and data analysis. The result of descriptive analysis showed positive response with class interval value 3.41 - <4.20 (